How does returning to work after retirement influence older workers' health? A scoping review protocol. Issue 3 (27th March 2019) - Lecours, Alexandra; Lord, Marie-Michèle; Negrini, Alessia; Robitaille, Rosalie
Abstract : Introduction: The return to the labour market after retirement is an increasing phenomenon in the North American population. It is the subject of a growing number of studies, whose conclusions seem inconsistent. As returning to working life after retirement is not neutral for individuals, the aim of this article is to present the protocol of a scoping review about its effects on older workers' health. Methods and analysis: The methodology of Arksey and O'Malley, including the recommendations of Levac et al and Daudt et al will be used. The process is composed of seven steps, from the identification of the research question, to the planning of knowledge transfer activities. Documents dealing with retirees returning to work in connection with health will be explored and analysed using the International Classification of Functioning, Disability and Health. Ethics and dissemination: Approval has been obtained for the consultation step of the protocol (ethics board of the Centre intégré universitaire en santé et service s sociaux de la Capitale Nationale, project #2019-1753). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols checklist will be used to support transparency and guide translation of findings. Findings will be shared with various stakeholders involved in older workers' health. Findings will also be disseminated in workshops, peer-reviewed journals and conferences.